Gingival Cyst of the Adult Involving Alveolar Mucosa and Gingiva: Case Report - Silva, Andreia Aparecida da; Cardoso, Camila Lopes; Silva, Evânio Vilela; León, Jorge Esquiche; Silveira, Heitor Albergoni da (ARCHIVES OF HEALTH INVESTIGATION, 2022)
The gingival cyst of the adult is an uncommon odontogenic cyst, etiologically related to the dental lamina. The aim of this study was to report a clinical case of gingival cyst of the adult. A 60-year-old male patient was referred to evaluate a lesion located in the anterior region of the left maxilla, close to the teeth #21 and #22. The patient’s medical history was not remarkable. Intraoral examination showed a nodular lesion covered by normal-appearing oral mucosa, asymptomatic, well-defined, with evolution of approximately 5 months. Since the periapical radiograph examination did not reveal any bone changes, the main diagnostic hypothesis was gingival cyst of the adult. By microscopy, typical features of gingival cyst of the adult were observed. The patient was monitoring and, after 3-year follow up, no signs of recurrence were demonstrated. Although rare, the gingival cyst of the adult should be considered in the differential diagnosis of any swelling involving the gingival region.